Identification and Comparison of Methicillin Resistance mecA Gene in Staphylococcus Aureus Isolated from Clinical Specimens Before and After Open Heart Surgery in Shariati Hospital in Tehran and in Dey Private Hospital - Marziyeh Sadat Amini; Faramarz Soleymanloo; Sajad Alizadeh; Hadi Feizi; Yashar Bagherizadeh; Mohammad Movagharnezhad; Mehdi Jahangiri-Hoseinabadi (Bihdād, 2018)
Background and Aim: Methicillin-resistant Staphylococcus aureus (MRSA) is one of the main causes of hospital infections. MRSA is resistant to all beta-lactams due to the presence of the mecA gene. The aim of this study was to isolate and identify the methicillin resistance gene of Staphylococcus aureus by PCR technique, before and after open heart surgery in Day and Shariati hospital. Materials and Methods: After collecting samples, various biochemical and microbiological tests were performed and then antibiotic susceptibility test using disc diffusion method based on CLSI instructions with antibiotics from different groups. It were used turned out to determine the resistance gene, PCR and Qpcr. Results: The results showed that the prevalence of mecA gene in clinical samples was 30% and there was a significant difference in the frequency of isolates of Staphylococcus aureus and MRSA in two hospitals of Day and Shariati. Among the antibiotics, the resistance before the operation of the open heart surgery was 95% for the oxacillin antibiotic and the antibiotic resistance after the surgery was higher than that for oxacillin 100%, erythromycin and, Ceftazidime 97%, which was tested more than the other antibiotics. Conclusion: Because of the importance of Staphylococcus aureus as the most important pathogenic pathogen and considering the significant reduction of MRSA isolation after open heart surgery in the private hospital of Day in comparison with Shariati Hospital, It can be concluded that it is likely that the environmental conditions and the principles of sterilization in private hospitals are much better than government hospitals.